Effectiveness of social work interventions in reducing deviant behaviour among secondary school students in Ibarapa Central Local Government, Igbo-Ora, Oyo State (2014)
The purpose of this study is to evaluate the effectiveness of intervention of school social work as a measure to be used in managing deviant behaviour among students in secondary schools. The study examined the type and most frequent deviant behaviours displayed by the students; and how deviant behaviour could be managed through social work intervention. The study employed descriptive survey method. An instrument, 'Deviant Behaviour and the Intervention of Social Workers Questionnaire' (DBISWQ) with r = 0.89 was used to collect data for the study. The population comprised all secondary schools students in Ibarapa Central Local Governments Area, Oyo State who have been referred to the School Guidance Counsellors for one problem or another. Three hundred respondents were randomly selected from five schools. Data collected were analysed using Analysis of Variance. The hypotheses were tested at 0.05 level of significance. The study revealed significant corrective effect of school social work intervention on the reduction of deviant behaviour among the students. Based on the findings, it was concluded that deviant behaviour could be reduced significantly by the intervention of school social workers. It was then recommended that school social workers should collaborate with Guidance Counsellors and be incorporated into school management personnel. Government should also establish the position of school social workers and reflect this in the National Policy on Education.